Strategi Pengembangan Potensi Desa dengan Pembuatan Klaster di Wilayah Kabupaten Bandung - Fitriani, F. Laksmi; Kurniawan, Iwan; Ahmad, Fandi (Pusat Pembelajaran dan Strategi Kebijakan Talenta Aparatur Sipil Negara Nasional, 2020)
The government provides stimulus in order to accelerate village-potential development through planned programs. However, development programs could not meet the target due to inability to maintain the diversity of current potentials. This study aimed to create village clusters in the Bandung Regency area based on village potentials and plan strategies to develop villages based on their clusters. The research used a mixed method approach (quantitative and qualitative). The sampling technique used non-probability sampling, namely saturated sampling. Data collected using secondary data from BPS, interview, and documentation. The data analyzed used cluster analysis with Two Step Clusters technique. The result was that villages in the Bandung Regency were categorized into five clusters. These clusters were based on demographic, geographic characteristics, and availability of public facilities, i.e. school, health, religious, market, bank/cooperation, leisure center, and tourism object. In addition, development strategy for the first cluster was promoting participative development plans. Second cluster needed development plans that strengthened human resource capacity, social capital, and public services. Finally, the third, fourth and fifth clusters had a similar strategy which focused on building financial, tourism, and leisure sectors to create more business areas.Â